Collins complete artist's manual the definitive guide to materials and techniques for painting and drawing - Jennings, Simon (London [England] HarperCollinsPublishers, 2013)
Following on from the tremendous international success of Collins Artist's Manual and Collins Art Class (more than 800,000 copies sold world-wide), we are taking the best of these books and creating a one-volume definitive reference book for all artists, whatever their level. Collins New Artist's Manual covers all the painting and drawing materials available to the artist today and also conveys the sheer joy and excitement of creating art. In addition, it contains a structured painting course from simple exercises to more advanced projects, with demonstrations by well-known practising artists who share their successes (and setbacks) with the reader
1
Keywords: Drawing -- Technique; Drawing -- Technique -- Handbooks, manuals, etc